Análisis del Edge Computing basado en Open Source como una solución de bajo costo para mejorar el rendimiento de la red de datos del gobierno autónomo descentralizado municipal del cantón Babahoyo. - Rizzo Riofrio, Byron Roberto (2022)
In the present investigation, it is desired to demonstrate through an extensive analysis of EDGE COMPUTING based on Open Source as a low-cost solution to improve the performance of the data network of the Autonomous Decentralized Municipal Government of the Babahoyo Canton, as a result, it is analyzed from information efficiently in order to improve the performance of the corporate network, optimizing the use of economic and natural resources through efficient and sustainable administrative, operational and financial management. To meet this objective, the current situation of the establishment was evaluated, determining as an object of investigation as well as the functional requirements, since this allows users to benefit from faster and more reliable institutional services, while the private sector currently benefits from the flexibility of the edge, in such a way that it becomes a competitive advantage. For data collection, it was necessary to use the following research technique: The interview addressed to Engineers about Edge computing in general. In turn, this project gives way to obtaining information that is necessary to improve the performance of the Babahoyo GAD data network. This investigative compendium reveals the need for Edge computing and according to the interview they mentioned that the use of an Edge seems ideal for services to be faster and more reliable. According to what was discussed in this investigation, the very necessary and important aspects of the Edge are deepened, which was investigative, explanatory thanks to the information provided by the environment.